Do lifestyle habits have an impact on infertility in couples? A systematic review of the topic - Cieślik, Aleksandra; Kosieradzka, Karolina; Kosecka, Katarzyna; Adamowicz, Dominik; Rudziński, Patryk; Jargieło, Anna; Łopuszyńska, Inga; Stańczyk, Justyna; Meliksetian, Astrik; Wosińska, Alicja (Journal of Education, Health and Sport, 2023)
Background: Infertility is a widespread concern that significantly impacts numerous couples in contemporary times. While the underlying causes of infertility often remain unknown, there is a growing interest in understanding the significant impact that modifiable lifestyle factors can have on its development. Lifestyle factors encompass various habits and ways of life that can be modified to improve overall health, including fertility. It is worth highlighting that these factors are under an individual’s control.They play a significant role in determining reproductive health and can positively or negatively influence the ability to conceive. Aim of study: The main purpose of this article is to review the recent research of this topic. It emphasizes the crucial importance for healthcare professionals to gain a thorough understanding of which lifestyle behaviors and habits can either adversely or positively impact fertility and use this knowledge to educate the patients. Material and methods: The work was based on the scientific literature and databases available on PubMed. The main used terms were „infertility” and „infertility and lifestyle”. Results and conclusions: Lifestyle factors, including smoking, alcohol consumption, drug use, stress or obesity have been implicated in the issue of male and female infertility. However, establishing a precise cause-effect relationship remains challenging due to the limited number of conducted studies and available literature on this topic. Nevertheless, there is a growing interest in this field, as infertility continues to be one of the most significant healthcare challenges worldwide, with rates of infertile couples on the rise.